Hubungan Body Image, Jenis Kelamin, Pola Konsumsi, dan Sikap dengan Status Gizi Remaja di SMAN 2 Martapura - Lillah Khofifah; Mahpolah Mahpolah; Rijanti Abdurrachim; Rosihan Anwar (HB PRESS, 2025)
Indonesia is currently focusing on improving nutrition at every stage of life, including adolescents who are vulnerable to nutritional status issues influenced by factors such as body image, gender, dietary patterns, and attitudes. In Banjar Regency, 30.11% of adolescents experience nutritional problems such as severely underweight, underweight, overweight, and obesity. This study aims to determine the relationship between these factors and the nutritional status of adolescents at Senior High School 2 Martapura. This research employed a cross-sectional design with a sample of 103 adolescents selected from a population of 814 using proportional random sampling. Data were collected through questionnaires and measurements of body weight and height. The results showed that most adolescents had normal nutritional status (64.1%), positive body image (60.2%), inadequate dietary patterns (62.1%), and positive attitudes (50.5%). Based on Fisher’s Exact test (?<0.05), gender showed a significant relationship with nutritional status (p = 0.039), and based on the Spearman Rank correlation test (?<0.05), dietary patterns were also significantly related to nutritional status (p = 0.020). However, body image (p = 0.667) and attitudes (p = 0.137) were not significantly related to nutritional status. Health institutions and schools are expected to actively monitor and provide nutrition education, while adolescents are encouraged to adopt balanced dietary patterns. Future researchers are advised to examine other factors affecting nutritional status.